Analysis of Learning Motivation and Learning Independence among Junior High School Students : A Case Study in Bengkulu - Cahyono, Maria Yuni Megarini (Sinergi International Journal of Psychology, 2025)
Indonesia’s persistent challenges in educational quality, highlighted by low PISA 2022 scores, have prompted the need to foster student centered learning environments that promote self directed learning (SDL). This study investigates the relationship between learning motivation and SDL among 150 junior secondary students from three public schools in Bengkulu, Indonesia. Utilizing a cross sectional correlational design, data were collected using validated scales: the Learning Motivation Scale and the Self Directed Learning Scale. Descriptive analyses indicated that most students were classified within the moderate range for both motivation and SDL. Assumption tests confirmed normality and linearity, allowing the use of Pearson’s correlation. Results showed a strong, positive, and statistically significant relationship between learning motivation and SDL (r = 0.784, p < 0.001). Discussion of findings emphasized the role of intrinsic motivation, contextual factors such as parental occupation and technology access, and the potential of project based learning models to enhance student autonomy. These insights suggest that interventions targeting motivational climates and resource availability can strategically foster SDL in junior secondary education. Future studies are encouraged to employ longitudinal methodologies to better understand the dynamic interplay between motivation and self regulated learning behaviors.